PENINGKATAN KEMAMPUAN LARI 60 METER MELALUI PERMAINAN TRADISIONAL BENTENGAN PADA SISWA KELAS V SEKOLAH DASAR - Nurhadi; Gatot Jariono; Nur Subekti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to improve the 60-meter sprint ability of fifth-grade students at SD Negeri Tegalmade 02 through the application of the traditional game Bentengan. The game incorporates elements of speed, strategy, and teamwork, which are expected to enhance the students' physical abilities, particularly in short-distance running. This study uses the Classroom Action Research (CAR) method with a quasi-experimental design involving pre-test and post-test to measure changes in students' running abilities. The subjects of the study were 21 students, consisting of 13 boys and 8 girls. The results indicate that the application of the Bentengan game significantly improved the students' 60-meter sprint performance, with an average reduction in time of around 1.5 seconds after the intervention. The game was proven effective in training acceleration, agility, and body coordination. Additionally, the Bentengan game also supports the development of muscle strength and teamwork, which contribute to overall physical performance improvement.